A CMOS 180 nm digitally adaptable bandgap voltage reference with integrated 7-bits voltage configurator for 5G wireless communication system - Nishant Kumaran; Selvakumar Mariappan; Jagadheswaran Rajendran; Selvarajah Krishnarajoo; Norhamizah Idros; Narendra Kumar; Asrulnizam A. Manaf (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
This paper proposes an adaptable bandgap voltage reference (BGR) with a 7-bits voltage configurator (7BVC) for 5G wireless communication integrated circuits. The 7BVC-BGR is designed and fabricated in a CMOS 180 nm process. The core BGR is integrated with 2-stage operational amplifiers (op-amp), buffers, and 7-bits digital switches. The 7BVC configures a set of current addition bits (A3-A0) and current subtraction bits (S2-S0) that control the total current flow into the load resistor. By controlling the seven digital bits, the 7BVC is capable of generating 128 states of voltage references (VREF), in which 92 states are optimum in its temperature coefficient (TC) and line regulation (LR). Supplied with a voltage headroom of 3.3 V, the 92 usable states provide a measured VREF that varies from 0.34 to 1.52 V. The TC and LR achieved by the varying VREF are 2.51 to 15.86 ppm/°C and 0.0089 to 0.0289 %/V, respectively. The power-supply-rejection-ratio (PSRR) achieved varies from -83.1 to -95.1 dB. The noise performance at 100 Hz varies from 4.9 to 19.8 µV/√Hz across the VREF configured. Also, the 7BVC-BGR can be reconfigured to improve the temperature coefficient (TC) by performing curvature correction and minimizing the VREF variations between samples. The 7BVC can be adjusted with various digital bit configurations to accommodate variations in TC and VREF values across samples. The proposed 7BVC-BGR exhibits consistent and reliable performance throughout testing and validation, placing it at the same level as the most advanced BGRs.